GAYA HIDUP MAHASISWI MIGRAN DAN NON MIGRAN DI KOTA PALEMBANG (Studi Kasus: Mahasiswi Migran dan Non Migran di Universitas PGRI Palembang) - Raden Ayu Wulantari; Armansyah Armansyah (Program Studi Kependudukan, Pascasarjana Universitas Sriwijaya, 2014)
, The number of female students in Indonesia, more than men. Programs student favorite is the economic, education and health. PGRI Palembang university campus is one that has the largest number of female students compared to other private university in the city of Palembang. Migrant Students have a complex problem because in terms of their status as women, especially regarding security. Conditions that make them to be away from their parents and relatives demanding that they should be able to withstand the problems independently. This study will examine the problem of student migrants through scientific study, entitled